1998
DOI: 10.1021/ja981687e
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hybrid Tetracenomycins through Combinatorial Biosynthesis Using a Glycosyltransferase Encoded by the elm Genes in Cosmid 16F4 and Which Shows a Broad Sugar Substrate Specificity

Abstract: Cosmid 16F4 contains 25 kb of the elloramycin biosynthetic pathway of Streptomyces olivaceus Tü2353. Transformation of this cosmid into a polyketide synthase (PKS)-deleted mutant of the urdamycin producer, Streptomyces fradiae Tü2717/ΔPKS and into the mithramycin producer Streptomyces argillaceus ATCC 12956 resulted in the production of several novel glycosylated tetracenomycins. Four of the structures of these elloramycin analogues (3, 5−7) were elucidated. They carry various deoxysugar moieties (d-olivose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The two constructs shown in this work (pOLV and pOLE) are the first two plasmids reported capable of synthesizing dTDP-activated sugars, and so they have the potential to be used for modifying different aglycones. This will require the use of "flexible" glycosyltransferases, and in this context, a few examples of glycosyltransferase substrate flexibility have been reported (8,46,61). The S. antibioticus OleG2 glycosyltransferase has been shown to transfer L-oleandrose and L-olivose (this work) and also L-rhamnose (12).…”
Section: Discussionmentioning
confidence: 85%
“…The two constructs shown in this work (pOLV and pOLE) are the first two plasmids reported capable of synthesizing dTDP-activated sugars, and so they have the potential to be used for modifying different aglycones. This will require the use of "flexible" glycosyltransferases, and in this context, a few examples of glycosyltransferase substrate flexibility have been reported (8,46,61). The S. antibioticus OleG2 glycosyltransferase has been shown to transfer L-oleandrose and L-olivose (this work) and also L-rhamnose (12).…”
Section: Discussionmentioning
confidence: 85%
“…A peak corresponding to RHA-TCMC (as compared with a standard) was observed in all of the experiments, indicating that the L-rhamnose was being synthesized and that the glycosyltransferase ElmGT was linking L-rhamnose to 8DMTC. In addition, some other peaks were found in the experiments in which the three methyltrans- (27). ElmMI, ElmMII, and Elm-MIII are described in this paper.…”
Section: Resultsmentioning
confidence: 67%
“…In this way, three glycosylated derivatives containing D-sugars were also tested. They were D-olivosyl-, D-mycarosyl-, and D-diolivosyl-tetracenomycin C. These compounds were produced by expressing cosmid 16F4 into the mithramycin producer S. argillaceus (27). When these compounds were individually fed into S. albus clones EPM1, EPM2, and EPM3, no new biotransformation products were found (data not shown), indicating that none of the methyltransferases act on D-sugars.…”
Section: Sugar Methylation During Elloramycin Biosynthesismentioning
confidence: 97%
“…Moreover, previous experiments also suggested that the glycosyltransferase ElmGT was not able to recognize TDP-D-oliose as a substrate. Thus, it has been shown that by expressing cosmid 16F4 in the mithramycin producer S. argillaceus, no D-oliosyl-tetracenomycin C was obtained, despite the fact that this microorganism synthesizes TDP-D-oliose (44).…”
Section: Discussionmentioning
confidence: 99%
“…Structure elucidation of D-digitoxosyl-tetracenomycin C and D-boivinosyl-tetracenomycin C. The two novel tetracenomycins were characterized by liquid chromatography-MS (see below) and NMR spectroscopy in comparison with various previously described 8-position glycosylated tetracenomycins and elloramycins (11,31,44).…”
Section: In Vivo Reconstitution Of Gene Clusters For the Biosynthesismentioning
confidence: 99%